The Efficiency of Regional Higher Education Systems and Competition in Russia - Leshukov, Oleg Valerievich; Platonova, Daria Pavlovna; Semyonov, Dmitry Sergeevich (Economy of Regions, 2016)
This paper explores the correlation between the degree of competition between higher education institutions (HEIs) and the efficiency of regional higher education systems using evidence from the Russian Federation. The choice of the regional system of higher education as a unit of analysis is explained by the features of the Russian system of higher education, especially by “closeness” in the borders of regions. We propose a special approach for the evaluation of the regional higher education system efficiency from the public administration perspective. Using data envelopment analysis (DEA), we investigate the efficiency of higher education systems in the regions and compare the results with the extent of higher education competition within them. The results indicate that higher efficiency scores and higher competition between HEIs in Russian regions are positively correlated. Moreover, by introducing socio-economic context status as a grouping parameter, we are able to specify the conditions of this relationship. The study explores that correlation between efficiency and competition is stronger in developing and low-performing regions. At the same time, higher education systems in developed regions consist of different HEIs, which create a competitive environment, although their efficiency level varies considerably. Taking into account all limitations of the study, these results contain several important issues for policy-making and higher education research discussions. They challenge the universalistic assumptions for the direction of higher education development.